System Performance of a Scalable 79 GHz Imaging MIMO Radar With Injection-Locked LO Feedthrough - Dominik Schwarz (IEEE Journal of Microwaves, 2021)
The estimation of the direction-of-arrival in a coherent multi-channel radar system requires the distribution of the high-frequency local oscillator signal to all hardware channels. Various system concepts with distribution network or feedthrough topologies are established. While distribution networks are bulky and costly, the time delays in systems with a feedthrough topology cause systematic errors in the range evaluation. In this work, a system concept based on an injection-locked feedthrough and the related radar system analysis is presented. The disadvantage of time delays in common feedthrough architectures can be eliminated by a hardware correction using the phase shifting capabilities of the injection-locked oscillator. In addition, two software correction algorithms are presented and analyzed. The performance of the realized system is shown by radar measurements and direction-of-arrival estimations. It is proven that the phase noise of different injection-locked oscillators is fully correlated within the radar system which results in the same detection performance as in state-of-the-art radar systems using a signal distribution network. Thus, the injection-locked feedthrough imaging radar topology is a suitable concept of realizing flexible radar frontends without bulky distribution networks.